Comparison of BMI Categories Using WHO 2007 and IAP 2015 Growth References Among Adolescent Girls - Dimple, Devilal; Ramesh, Gowri (Asian Journal of Biological and Life Sciences, 2025)
Introduction: World Health Organization (WHO) 2007 growth references and Indian Academy of Pediatrics (IAP) 2015 growth references are the two most popular indices used to identify malnutrition among children and adolescents in India. However, they are not in sync in identifying malnutrition among children and adolescents. Hence, this study aimed to compare the Body Mass Index (BMI) categories based on WHO 2007 growth references and IAP 2015 growth references among adolescent girls and to associate their total body fat percentage. Materials and Methods: This cross-sectional study recruited 536 adolescent girls aged 10 to 15 years from private and state-run schools in Chennai, India. Height, Body Weight, and total body fat percentages were recorded. BMI-for-age z-scores were calculated. Statistical analysis included the x2 test, t test, and Pearson’s correlation. p<0.05 was considered for statistical significance. Results: There was a significant difference (p<0.001) in the BMI categorization based on both the growth references. Thinness, as observed by WHO 2007 growth references, was four times higher than the IAP 2015 growth reference. IAP 2015 growth reference identified nearly 1/3rd of the participants to have overweight or obesity, whereas the WHO 2007 growth reference identified almost 1/4th of the participants to have overweight or obesity. The mean total body fat percentage in all categories was higher with WHO 2007 growth references categorization (p<0.05). Conclusion: The WHO 2007 growth references over-predicted thinness and under-predicted overweight compared to IAP 2015 growth references.
Keywords: Double burden of malnutrition; Growth charts; Obesity; Thinness